2013
DOI: 10.1111/lam.12030
|View full text |Cite
|
Sign up to set email alerts
|

Presence of indicator bacteria, diarrhoeagenic Escherichia coli pathotypes and Salmonella in fresh carrot juice from Mexican restaurants

Abstract: Coliform bacteria (CB), faecal coliforms (FC), Escherichia coli, diarrhoeagenic E. coli pathotypes (DEP) and Salmonella frequencies were determined for fresh carrot juice from restaurants in Pachuca city, Mexico. Two hundred and eighty carrot juice samples were purchased in three types of restaurants: (A), national chain restaurants; (B), local restaurants; and (C), very small restaurants. Two restaurants for each A and B, and three for C, were included. Forty juice samples were purchased at each restaurant. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 30 publications
5
20
0
Order By: Relevance
“…Similar results showing the lack of 0157 and H7 antigens in STEC strains isolated in Mexico have been reported (9). STEC strains have been identified from raw foods in Mexico such as vegetable salads (3) and carrot juice (27).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Similar results showing the lack of 0157 and H7 antigens in STEC strains isolated in Mexico have been reported (9). STEC strains have been identified from raw foods in Mexico such as vegetable salads (3) and carrot juice (27).…”
Section: Resultssupporting
confidence: 70%
“…These pathogens usually are transmitted by contaminated food. The ETEC pathotype has been isolated from raw vegetable salads (3) and carrot juice (27). EPEC is a leading cause of diarrhea in developed countries (9,28).…”
Section: Resultsmentioning
confidence: 99%
“…For the STEC, only the stx2 locus was detected in one strain, the stx\ locus was detected in three strains, and both stx\ and stx2 were detected in one strain ( Table 2). STEC strains have been identified from raw foods in Mexico, including vegetable salads (5) and carrot juice (46). The pathogenesis of STEC is linked to different virulence factors, such as Shiga toxins (the products of stxi and stx2) (35).…”
Section: Methodsmentioning
confidence: 99%
“…Results showed that 99% of the analyzed RTE salads were contaminated with fecal coliforms; 85% harbored E. coli and 7% diarrhoeagenic E. coli pathotypes (DEPs) . Moreover, 96.8% of analyzed juices were contaminated with fecal coliforms, 53.6% harbored E. coli, 8.9% DEPs, and 8.6% were positives for Salmonella (Torres-Vitela et al, 2013). The fact that almost all salads and juices samples were contaminated with fecal matter regardless of the status of hygiene of the restaurants, it may be because most vegetables consumed in Pachuca-City are grown in the Mezquital Valley.…”
Section: Sources Of Contamination Irrigation Watermentioning
confidence: 96%
“…The fact that almost all salads and juices samples were contaminated with fecal matter regardless of the status of hygiene of the restaurants, it may be because most vegetables consumed in Pachuca-City are grown in the Mezquital Valley. Thus, contamination most likely originated from irrigation water rather than from poor sanitation practices at the restaurants (Torres-Vitela et al, 2013).…”
Section: Sources Of Contamination Irrigation Watermentioning
confidence: 99%